Numerical and observational study of an event of decrease in the total ozone column of tropical origin in Southern Brazil - Guzmán, Lissette (2020)
A depletion event of 11% of the total ozone column over South Brazil was analyzed from observational data and numerical simulations. The meteorological fields resulting from the simulation did not show the presence of subtropical or polar jets over the study region. The real and simulated soundings showed the dryness at high and low tropospheric levels, pointing a stratospheric intrusion. The total ozone column values from ERA-5 reanalyses showed the maintenance of a region with low total ozone values in tropical latitudes and its advance over the study region, before and during the depletion event. The isentropic retro-trajectories of air parcels at different levels, obtained with the Hybrid Single Lagrangian Integrated Trajectory Model (HYSPLIT), confirmed the zonal transport from the tropical region over Southern Brazil. A combination of a cyclonic circulation at the 850 K stratospheric isentropic level and an intense anticyclonic circulation at the 440 K tropospheric level, over the depletion region, was identified as responsible for the tropopause lift and horizontal transport of ozone-rich air out of the column.